Hubungan Kualitas Tidur dengan Kadar Hemoglobin pada Remaja Putri Alumni Angkatan 25 di Sekretariat Pondok Pesantren Darul Salam Kota Singkawang - Syarifah, Syarifah; Adi Saputra, Supriyana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The need for sleep in a person is a basic need which, if not fulfilled properly, will cause several health problems. Anemia is a condition where hemoglobin levels are below normal. To determine the relationship between sleep quality and Hemoglobin levels of female adolescents’ alumni of class 25 Darul Salam Islamic Boarding School, Singkawang City. This study used an observational analytic research design with a cross-sectional approach. Results: The research was conducted in March - May 2023 on 30 respondents by means of a questionnaire. The study was conducted in March. The results of this study showed that there was a significant relationship between sleep quality and hemoglobin levels (p = 0.043). Conclusion: 9 girls (30%) had normal hemoglobin levels, while 21 girls (70%) had below normal hemoglobin levels